A Model for Estimating the Burden of Disease of Transfusion-Transmitted Infection - Riley, William; Love, Kailey; Saxon, Mary; Tobian, Aaron; Bloch, Evan M.; Kasirye, Ronnie; Lubega, Irene; Musisi, Ezra; Dhabangi, Aggrey; Kyeyune, Dorothy; McCullough, Jeffrey (International Journal of Public Health, 2024)
Objectives: Blood transfusion is an important mode of infectious disease transmission in low-and middleincome countries (LMICs). This study describes a model to determine the prevalence of Transfusion Transmitted Infections (TTIs) and the associated burden of disease.Methods: A five-step model was developed to determine the TTI-related burden of disease measured by Disability Adjusted Life Years (DALYs). Uganda was selected as the study country.Results: Approximately 298,266 units of blood were transfused in Uganda in 2019, yielding an estimated TTI incidence of 6,858 new TTIs (2.3% of transfused units) and prevalence of 19,141 TTIs (6.4% of transfused units). The total burden of disease is 2,903 DALYs, consisting of approximately 2,590 years of life lost (YLLs), and 313 years living with disability (YLDs).Conclusions: The incidence and prevalence of TTIs and the associated burden of disease can be calculated on a local and national level. The model can be applied by health ministries to estimate the impact of TTIs in order to develop blood safety strategies to reduce the burden of disease.